Study of trace elements in groundwater of Western Uttar Pradesh, India - Mohammad Muqtada Ali Khan; Rashid Umar; Habibah Lateh (Academic Journals, 2010)
Indo-Gangetic plain encompassed a large alluvial track consisting of multi-tier aquifer system. Due to stride developmental activities and agricultural advancement, shallow groundwater regime was under potential threats to get contaminated. In the present study, ‘DRASTIC’ methodology was adopted to demarcate the zones based on their vulnerability to contamination. In CGP, both quality and quantity of shallow aquifers to a large extent was governed by land use pattern. Therefore, landuse pattern was included in the widely applied ‘DRASTIC’ methodology. The landuse pattern was classified into different categories, for example, industrial, agriculture and rural and a numeric rating was assigned for each category based on probable risk. The model provided a numerical basis for estimating vulnerability indices and the map that is thus prepared depicts that 5, 39, 33 and 23% of the area studied correspond to low, moderate, high and very high vulnerable zones, respectively. As chemical studies unequivocally demonstrated that pollution is the major source of solutes in groundwater, a good match between TDS values and vulnerability indices gave credibility in the estimation of vulnerability to contamination.